2017
DOI: 10.18632/oncotarget.19622
|View full text |Cite
|
Sign up to set email alerts
|

EGF stimulates glioblastoma metastasis by induction of matrix metalloproteinase-9 in an EGFR-dependent mechanism

Abstract: Epidermal growth factor (EGF) and EGF receptor (EGFR) play prominent roles in the metastasis of glioblastoma (GBM). However, the molecular mechanisms for the function of EGF and EGFR in GBM metastasis have not been elucidated. Herein, we demonstrate that coactivation of EGF and EGFR drives tumor metastasis in a matrix metalloproteinase-9 (MMP-9)–dependent manner. Expression levels of EGF, EGFR, and MMP-9 were substantially upregulated in the GBM and edema zones of patients, compared with those of paired unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Moreover, inhibition of GBM cells by EGFR is associated with anti-angiogenic and pro-apoptotic effects on the tumor [72]. It has been reported that coactivation of EGF and EGFR drives tumor metastasis via PI3K/AKT-dependent pathways [73]. Targeting FAK/STAT3 sensitizes gliomas to the anti-EGFR agent gefitinib and alkylating agent temozolomide in human gliomas [74].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of GBM cells by EGFR is associated with anti-angiogenic and pro-apoptotic effects on the tumor [72]. It has been reported that coactivation of EGF and EGFR drives tumor metastasis via PI3K/AKT-dependent pathways [73]. Targeting FAK/STAT3 sensitizes gliomas to the anti-EGFR agent gefitinib and alkylating agent temozolomide in human gliomas [74].…”
Section: Discussionmentioning
confidence: 99%
“…Equipped with this functional background, tumor cells alternate with macrophages along extra cellular matrix fibers until they reach blood vessels where macrophages facilitate the entry of tumor cells across the vessel wall [ 138 , 139 ]. Moreover, it is known that EGF plays a role in the metastasis of glioblastoma by induction of matrix metalloproteinase-9 in an EGFR-dependent mechanism [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 and EGFR are both present in the cerebrospinal-fluid (CSF) of patients and their levels decline after tumour resection. MMP-9 transcription is stimulated by EGFR and EGFRvIII in glioblastoma, with signalling pathways involved such as PI3K/AKT (PKB), STAT3/5, NFk-B, ERK and Sonic hedgehog (SHH) [44][45][46]. MMP-9 can cleave several ECM components, preferentially type IV collagen, gelatine, and elastin; but also, regulates cell-ECM interactions: MMP-9 is able to act on cell motility via direct cleavage of CD44, a surface glycoprotein involved in cell-ECM interactions via binding to several ECM ligands, mainly hyaluronic acid.…”
Section: Mmp-9 In Glioblastoma Progressionmentioning
confidence: 99%